Knockdown GTSE1 enhances radiosensitivity in non–small‐cell lung cancer through DNA damage repair pathway. Issue 9 (22nd March 2020) - Lei, Xiao; Du, Lehui; Zhang, Pei; Ma, Na; Liang, Yanjie; Han, Yanan; Qu, Baolin
Abstract: Radiotherapy is an important strategy for NSCLC. However, although a variety of comprehensive radiotherapy‐based treatments have dominated the treatment of NSCLC, it cannot be avoided to overcome the growing radioresistance during radiotherapy. The purpose of this study was to elucidate the radiosensitizing effects of NSCLC via knockdown GTSE1 expression and its mechanism. Experiments were performed by using multiple NSCLC cells such as A549, H460 and H1299. Firstly, we found GTSE1 conferred to radioresistance via clonogenic assay and apoptosis assay. Then, we detected the level of DNA damage through comet assay and γH2AX foci, which we could clearly observe knockdown GTSE1 enhance DNA damage after IR. Furthermore, through using laser assay and detecting DNA damage repair early protein expression, we found radiation could induce GTSE1 recruited to DSB site and initiate DNA damage response. Our finding demonstrated that knockdown GTSE1 enhances radiosensitivity in NSCLC through DNA damage repair pathway. This novel observation may have therapeutic implications to improve therapeutic efficacy of radiation.